The Virtual Fence Dynamic: a Breakthrough for Low-Cost and Sustainable Mitigation of Human-Elephant Conflict in Subsistence Agriculture? - La Grange, Michael; Matema, Collen; Nyamukure, Bella; Hoare, Richard (Frontiers in Conservation Science, 2022)
Attempts to deter elephants from entering crop fields and human settlements in Africa have used various barriers (e.g. electric fences, chilli fences, beehive fences or plant barriers), situated on or very near the boundaries of fields or villages, with rather variable success. We explored a very simple new barrier concept based upon re-arranging the layout of foreign stimuli already known to arouse suspicion and fear among elephants. Deterrence involved deploying unnaturally scented objects on and across their pathways of habitual movement leading to crop field clusters. Elephants are suspicious of unpleasant olfactory stimuli, like string or cloth saturated with pungent-smelling chilli oil, old engine oil, or creosote and dislike ‘chilli smoke’. Foreign visual items like plastic bottles, reflective metal strips and cow bells possibly reinforced suspicion of these unpleasant scents and influenced the deterrent effect. These flimsy items deployed over very short distances merely acted as a bluff to ‘problem elephants’ that people were actively trying to impede their progress, and the vast majority chose to turn back or deviate substantially. Thus we coined the term a ‘soft virtual boundary’. We demonstrate that placing virtual boundaries away from village and agricultural lands, forces elephants to encounter them upon leaving their daytime refuges, while still in natural habitat. The suspicion and fear generated here considerably reduces elephants’ determination to proceed onwards to risk crop raiding. When multiple, small virtual boundaries are strategically moved around at intervals, a ’virtual fence dynamic’ delivers an enduring deterrent effect. In ten study areas in two countries over seven years this technique led to considerable and consistent reductions in crop damage levels of up to 95% in places. Because these methods (i) completely rely on local knowledge, (ii) were exceptionally low cost and (iii) demonstrated rapid results, the ‘buy-in’ from affected communities of small-scale subsistence farmers was immediate and very enthusiastic. So this strategy has the potential to remove the most intractable stumbling block to the sustainability of human-elephant conflict mitigation efforts in smallholder agriculture – reliance upon conservation donor funding for very costly and problematic mitigation measures like fencing, compensation schemes and elephant translocations.